2022
DOI: 10.3389/fpls.2022.1066752
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study reveals quantitative trait loci for waterlogging-triggered adventitious roots and aerenchyma formation in common wheat

Abstract: Waterlogging severely affects wheat growth and development. Limited availability of oxygen in the root zone negatively affects the metabolism of plants. The formation of adventitious roots (ARs) and root cortical aerenchyma (RCA) are the most important adaptive trait contributing to plants’ ability to survive in waterlogged soil conditions. This study used a genome-wide association study (GWAS) approach with 90K single nucleotide polymorphisms (SNPs) in a panel of 329 wheat genotypes, to reveal quantitative tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…In wheat plants waterlogged at the vegetative stage, a single QTL (on chromosome 1BL) was associated with the variation in chlorophyll content [24]. However, other authors [25] reported the identification of three QTL on the same chromosome and one on chromosome 1D that account for the phenotypic variation in chlorophyll content. A gene linked to a QTL located on chromosome 2B and its involvement in the degradation of reactive oxygen species (ROS) was also identified during waterlogging [25].…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…In wheat plants waterlogged at the vegetative stage, a single QTL (on chromosome 1BL) was associated with the variation in chlorophyll content [24]. However, other authors [25] reported the identification of three QTL on the same chromosome and one on chromosome 1D that account for the phenotypic variation in chlorophyll content. A gene linked to a QTL located on chromosome 2B and its involvement in the degradation of reactive oxygen species (ROS) was also identified during waterlogging [25].…”
Section: Introductionmentioning
confidence: 95%
“…In the AdvL-4, the ZGS of WW plants corresponded with the spike emergence stage, progressing to the anthesis stage (ZGS 60-69) in WL plants. Despite all the genotypes facing the same 14-day period of waterlogging, which started at the same developmental growth stage (Tillering, ZGS [22][23][24][25], their growth rate was not uniform. This resulted in nine genotypes being waterlogged during tillering and stem elongation (PL-1, PL-3, PL-5, IT-3, GR-1, GR-2, GR-3, AdvL-2, and AdvL-3), while others also experienced stress during the booting stage (PL-4 and Austrl-5).…”
Section: Changes In Phenotypic Development During Waterloggingmentioning
confidence: 99%
See 1 more Smart Citation